2021
DOI: 10.1242/jcs.255752
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of APP endocytosis by neuronal aging drives amyloid-dependent synapse loss

Abstract: Neuronal aging increases the risk of late-onset Alzheimer's disease. During normal aging, synapses decline, and β-amyloid (Aβ) accumulates intraneuronally. However, little is known about the underlying cell biological mechanisms. We studied normal neuronal aging using normal aged brain and aged mouse primary neurons that accumulate lysosomal lipofuscin and show synapse loss. We identify the up-regulation of amyloid precursor protein (APP) endocytosis as a neuronal aging mechanism that potentiates APP processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(77 citation statements)
references
References 159 publications
(233 reference statements)
5
70
2
Order By: Relevance
“…Furthermore, using typical AD biomarkers (Aβ accumulation, reactive astrocytes, and dystrophic neurons), we did not find close similarities between young AD and aged WT mice. We cannot exclude that in the latter, other changes in astrocytes and microglia as well as subthreshold amount of Aβ or other products of the APP processing may be sufficient to induce the observed network alterations [ 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using typical AD biomarkers (Aβ accumulation, reactive astrocytes, and dystrophic neurons), we did not find close similarities between young AD and aged WT mice. We cannot exclude that in the latter, other changes in astrocytes and microglia as well as subthreshold amount of Aβ or other products of the APP processing may be sufficient to induce the observed network alterations [ 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we observed the same profile in human brain samples, in which we established a positive correlation between APP processing and aging. Considering the previously described accumulation of CTFs (Burrinha et al, 2021) and increased BACE1 activity (Fukumoto et al, 2004) in aged mice, we postulate that APP-derived amyloidogenic fragments accumulate and alter NMDAR function. To test this hypothesis, we used a β-secretase 1 (BACE 1) inhibitor in aged animals to block the APP amyloidogenic processing, which resulted in a decrease in GluN2B synaptic contribution of about 20%, getting closer to the results obtained in adult mice.…”
Section: Discussionmentioning
confidence: 81%
“…The aging impact on APP processing is likely independent of cellular APP levels alterations, which we found unaltered. APP endocytosis was shown to be upregulated in aging, thus favouring APP processing through the amyloidogenic pathway (Burrinha et al, 2021). We therefore blocked APP amyloidogenic processing in aged mice by oral administration of a β-secretase 1 (BACE 1) (BI) inhibitor (LY2811376; 100mg/kg), 12 h prior to patch-clamp recordings ( Figure 4i, j ).…”
Section: Resultsmentioning
confidence: 99%
“…Cell and systems biology studies have reported disturbances in the autophagy and endolysosomal pathways as initial molecular changes in sporadic and familial AD cases, suggesting defects in these pathways underlying AD pathogenesis [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In line with these results, APP, the amyloid precursor protein, is a transmembrane protein situated in the cell membrane and several organelles, including endosomes and autophagic vesicles, indicating that failures in autophagy endolysosomal activities contribute to the amyloid β accumulation [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 77%